Effectiveness of Experimental Tools for Testing the Permeability of Metal Materials to Increase Student Learning Motivation - Ernidawati, Ernidawati; Darmadi, Darmadi; Fauza, Naila; Idris, Idris; Syaflita, Dina; Junaidi, M.; Sundari, Putri Dwi (Journal of Natural Science and Integration, 2025)
This study investigates the effectiveness of an experimental apparatus designed to measure the permeability of metal materials as an instructional medium for enhancing the learning motivation of 12th-grade science students on the topic of magnetic fields. The research was conducted at SMAIT Al Fityah Pekanbaru and MA Darul Hikmah Pekanbaru, involving 20 students from each institution. The apparatus was specifically developed to facilitate hands-on exploration of magnetic permeability in various metals. Employing a pre-experimental method, the study adopted a Pretest-Posttest Group Design to assess changes in student motivation. Data were collected using a validated ARCS learning motivation questionnaire, which evaluates four components: Attention, Relevance, Confidence, and Satisfaction. Motivation scores were recorded before and after the intervention, and the results were analyzed descriptively using normalized gain (N-Gain) and its corresponding percentage. The findings revealed a significant improvement in students’ motivation following the use of the experimental tool. The N-Gain percentage reached 86%, surpassing the established threshold for effectiveness (>75%). These results indicate that the tool is not only functional but also pedagogically effective in fostering increased motivation in learning physics, particularly in understanding abstract concepts such as magnetic permeability.Keywords : effectiveness, experimental tools, metallic materials motivation, testing permeability